Science without borders: from the icy expanses of the North to Chinese megacities - Cherkashina E.V.; Kudrin E.P.; Druzyanov I.I.; Okhlopkov P.P. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyze and summarize the research conducted within the framework of the scientific school on the problems of physical culture and sports in the Sakha Republic. Methods and structure of the study. An analysis of scientific and methodological literature, a method of comparison and contrast, theoretical analysis and analytical review of scientific publications and the results of intellectual activity obtained within the framework of the scientific school of the Republic of Sakha were conducted. Results and conclusions. From 2011 to 2025, research on the theory and methodology of training athletes in mas-wrestling, Thai boxing, basketball, golf and athletics was carried out within the framework of the FKiS scientific school in Yakutia. In addition, the history and development of the Yakut national wrestling khapsagai, as well as issues of ethnopedagogical education of a healthy lifestyle and recreational physical culture were studied. During this period, seven dissertations were defended, including six candidate’s and one doctoral dissertations, in specialties related to the theory and methodology of physical education, sports training, general pedagogy and the history of pedagogy.